Serum CXCL13 as a Novel Biomarker in Oral Squamous Cell Carcinoma - Shin Tojo; Koh‐ichi Nakashiro; Nobuyuki Kuribayashi; Daisuke Uchida (Cancer Medicine)
Abstract Background Despite its low sensitivity (approximately 30%), squamous cell carcinoma (SCC) antigen is commonly utilized as a serum tumor marker for oral SCC (OSCC) in clinical settings. The objective of this research was to identify novel biomarkers for OSCC. Methods Initially, we performed microarray analysis to evaluate the gene expression signatures of primary OSCC and normal oral mucosal tissues. Our findings showed the C‐X‐C motif chemokine ligand 13 (CXCL13) to be a promising novel biomarker as it was consistently overexpressed in primary OSCC tissues, a conclusion corroborated by polymerase chain reaction results. Subsequently, we measured serum CXCL13 levels in 125 patients with OSCC using a sandwich enzyme‐linked immunosorbent assay and compared the results with those of 29 healthy individuals. Results Remarkably, the levels of serum CXCL13 were consistently elevated in patients with OSCC, and the high expression of serum CXCL13 was notably associated with tumor size and neck lymph node metastasis. Patients with advanced OSCC with high‐serum CXCL13 levels exhibited poor prognosis regarding both overall and disease‐free survival. Finally, spatial transcriptome analysis revealed CXCL13 and CD8 expressions within tumor area clusters but not in adjacent normal areas, suggesting specific overexpression of CXCL13 in primary OSCC tissues. Conclusion These findings imply that serum CXCL13 holds diagnostic and prognostic value, showing promise as a novel biomarker for OSCC.